Characterization With Gene Mutations in Han Chinese Patients With Hypospadias and Function Analysis of a Novel AR Genevariant - Chen, Lifen; Wang, Junqi; Lu, Wenli; Xiao, Yuan; Ni, Jihong; Wang, Wei; Ma, Xiaoyu; Dong, Zhiya (Frontiers in Genetics, 2021)
It is estimated that around 10%-20% of hypospadias are caused by genetic abnormalities worldwide although the spectrum of associated genes does vary across different ethnicities. The prevalence of hypospadias among the Chinese population has been increasing the last couple of decades. However, the pathogenesis underlying the disease and its associated genetic abnormality remains unclear. Here we performed a genetic analysis of 81children with karyotype 46, XY and the hypospadias phenotype in order to characterize the genetic components that contribute to the development of hypospadias in Chinese patients. 15 candidate genes, including sex determination genes-SOX9, SRY, NR0B1 (DAX1), NR5A1 (SF1), DHH, sex differentiation genes-AR, SRD5A2, MAMLD1, INSL3, and hypospadias-associated genes-FGF8, FGF10, BMP4, BMP7, ATF3, and MID1 were screened by using next generation sequencing. A total of 18 patients were found to have mutations identified by PCR and sequencing, including 11 cases of SRD5A2 genes, 6 cases of AR genes, and 1 case of MID1 gene, respectively. One novel missense mutation p.I817N was discovered in AR gene. Further molecular analysis found that subcellular localization of the ARI817N was the same as that of wild type ARWT in the absence or presence of hormone. But it led to 50% reduction in AR-induced transcriptional activity in the presence of either the synthetic androgen R1881 or the natural ligand dihydrotestosterone. Our results indicate that SRD5A2 and AR genes are two top candidate genes associated with 46, XY hypospadias in Chinese patients. Further epidemiological and genetic analysis are still needed to further clarify the pathogenesis of hypospadias in Han Chinese patients.